Akulturasi Islam dan Peradaban Melayu dalam Tradisi Kelahiran Orang Melayu Palembang - Haljuliza Fasari P (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2019)
This article discusses how Islam perceived, developed, and practiced in the context of birth traditions by the Malays-Palembangnese. On the one hand, Islam inluences the local traditions and Islam Impact each other. Resulting in modifications that are represented by particular symbols. Through a qualitative study with Geertz interpretive approach, this articel proves that the acculturation process occurs between Islam and Malay-Palembangnese culture on birth tradition practices; the process of the spread of Islam in Malay-Palembangnese society happens contestatively and gradually; and the Malay-Palembangnese form of religiosity in the context o birth traditions does not possess a single characteristic in contrast to the ideas proposed by Geetrz’s, Woodward’s, Nur Syam”s, and Ricleft’s Theories.